Conducting a Water Safety Plan (WSP) Relied on WHO Recommendations for the Assessment of Qom Desalinated Water Supply System - Shahla Shafiei; Mohammad Khazaei; Ramin Nabizadeh; Mohammad Fahiminia; Mostafa Leili; Vahid Razmju; Reza Ansari; Mina Aghaei (Hamadan University of Medical Sciences, 2017)
This work aimed to apply the water safety plan (WSP), a plan suggested by the World Health Organization (WHO), to evaluate desalinated water supply system in Qom province of Iran, assisting a systematic prevention approach based on risk assessment. Major portion of Qom drinking water is supplied by an integrated membrane-based desalination system through a private water network. WSP includes 12 phases comprising chapters like "System Description", "Hazard Identification", and "Risk Assessment". The abovementioned phases were conducted according to filled checklists which finally served as the input data for WSP software, namely WSP QA Tool. The processed information by the software attributed to each step was presented finally as appropriate tables and histograms. Total score obtained for Qom desalinated water supply system via WSP was 302 whereas, the full obtainable score considered in WSP was 440. Accordingly, 68.6% of the total WSP obtainable scores was acquired. The scores achieved in steps "catchment", "treatment", "distribution", and "point of use" were 67%, 67%, 64%, and 65%, respectively. The minimum obtained score was 25% assigned to the step "Improvement Plan". The maximum scores were 100% and 97% attributed to "Identification of Stakeholders" and "Hazard Identification and Risk Assessment", respectively. The score of 68.6% from WSP was achieved by Qom desalinated water supply system. The step "Improvement Plan" should be performed simultaneously with the entire WSP to improve the coordination for better enforcement of the plan. To enhance the current condition, the funding demands assigned to each uncontrolled risk which is attributed to each improvement program must be supplied, ranked, and enforced.